Single-use vape batteries: investigating their potential as ignition sources in waste and recycling streams - Gausden, Andrew; Cerik, Burak Can (MDPI, 2024)
This study investigates the potential link between the increasing prevalence of single-use vapes (SUVs) and the rising frequency of waste and recycling fires in the UK. Incorrectly discarded Li-ion cells from SUVs can suffer mechanical damage, potentially leading to thermal runaway (TR) depending on the cells’ state of charge (SOC). Industry-standard abuse tests (short-circuit and nail test) and novel impact and crush tests, simulating damage during waste management processes, were conducted on Li-ion cells from two market-leading SUVs. The novel tests created internal short circuits, generating higher temperatures than the short-circuit test required for product safety. The cells in used SUVs had an average SOC ≤ 50% and reached a maximum temperature of 131 °C, below the minimum ignition temperature of common waste materials. The high temperatures were short-lived and had limited heat transfer to adjacent materials. The study concludes that Li-ion cells in used SUVs at ≤50% SOC cannot generate sufficient heat and temperature to ignite common waste and recycling materials. These findings have implications for understanding the fire risk associated with discarded SUVs in waste management facilities.
Keywords: lithium-ion cells; thermal runaway; battery abuse testing; e-cigarettes; nail test; battery impact test